Control Room Design Review Guidance: Technical Criteria Updates. (September 2014) - O'Hara, John; Higgins, James; Fleger, Stephen
The U.S. Nuclear Regulatory Commission (NRC) evaluates the human factors engineering (HFE) of nuclear power plant design and operations to protect public health and safety. The HFE safety reviews encompass both the design process and its products. Detailed guidance for these reviews is provided in two key documents: the HFE Program Review Model (NUREG-0711) and the Human-System Interface Design Review Guidelines (NUREG-0700). The NRC is committed to the periodic update and improvement of the guidance to ensure that they remain state-of-the-art design evaluation tools. In this paper we will describe the guidance development and update methodology and the topics being addressed for both key documents. The guidance update program will improve document usability as well.